The effect of housing development during financial crisis: A case of Malaysia in 1997 to 2002 / Suhaila Abu Gani (Abd Gani) - Abu Gani (Abd Gani), Suhaila (2007)
This study was examined how housing development was influenced by inflation rate, interest rate and cost of construction during financial crisis. It also was analyze the relationship between housing development and independent component (inflation rate, interest rate and cost of construction). This study was also determined whether the independent component give strong influenced towards housing development. Specifically there are four objectives of this study. The objectives of this study are to study the effect of financial crisis towards housing development during financial crisis from 1997 to 2002, to investigate the effect of interest rate towards housing development during financial crisis from 1997 to 2002, to investigate the effect of consumer price index towards housing development during financial crisis from 1997 to 2002 and to investigate the effect of cost of construction towards housing development during financial crisis from 1997 to 2002. This study estimated monthly multiple regressions for 5 year period beginning 1997 to 2002 and used R2 as the primary metric to measure value-relevance to explain the variation occur in the dependent variable by independent variable. Multiple Regressions Method was conducted on the equations in order to test the three hypothesis of this research. The result of this research shows that inflation rate is no significantly associated with the housing development. While, interest rate and cost of construction show significant associated with housing development. This study also provides the evidence that inflation rate, interest rate and cost of construction is significantly and no significantly associated with housing development.